Penyuluhan Keamanan Pangan sebagai Upaya Pemberdayaan UMKM Kue Baruasa di Desa Tapulaga, Kecamatan Soropia, Kabupaten Konawe - Zainab Hikmawati; Arum Dian Pratiwi; Siti Rabbani Karimuna (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Traditional food-based micro, small, and medium enterprises (MSMEs) such as Kue Baruasa play an important role in household income and the preservation of local culinary heritage, yet their sustainability strongly depends on the application of food safety principles in the production process. A preliminary survey of the Baruasa Mama Eda MSME in Tapulaga Village, Soropia Subdistrict, Konawe Regency found that partners' understanding of hygiene sanitation and Good Manufacturing Practices for processed food (CPPOB) remained low. This community service activity aimed to improve the knowledge and skills of MSME partners regarding food safety principles through direct counseling. The implementation method involved coordination with the local village and subdistrict government, face-to-face counseling covering the five keys to food safety, the CEK KLIK product-checking strategy for purchasing raw materials, safe food storage and processing techniques, and control of biological, chemical, and physical contamination, followed by an evaluation using pre-test and post-test questionnaires administered to 40 partner respondents. The results showed an increase in the average knowledge score on the food safety and CPPOB aspect from 37.5% (pre-test) to 99.5% (post-test), the highest gain among the program components. Overall, partners' average knowledge score increased from 43.17% to 99.67%, with all 40 respondents (100%) falling into the